Character Development Through Physical Learning For Elementary School Children - Febryani, Febryani; Marheni, Eddy; Damrah, Damrah; Bahtra, Ridho; Andika, Heru; Ockta, Yovhandra (STKIP Singkawang, 2024)
This study aims to analyze the effectiveness of Physical Education (PE) learning in instilling and familiarizing positive character values in elementary school children. Character education is becoming increasingly important in the challenging era of globalization, where the flow of foreign cultures and the influence of social media can hinder the development of children's character. This study uses a descriptive qualitative approach involving 20 students, 5 parents of students, 2 teachers, and 1 principal at Elementary School Angkasa I Lanud Sutan Syahrir Padang. Data were collected through observation, unstructured interviews, and documentation studies. The results of the study indicate that PE activities are an effective medium in instilling character values such as discipline, cooperation, and responsibility. Teachers act as role models in teaching these values, while parental support strengthens character habits outside of school. Although effective, there are several challenges in its implementation, such as time constraints and lack of training for teachers. This study conveys that PE has great potential to contribute to the formation of a young generation that is not only physically healthy but also strong in character.